Strategi Humor Gibran Rakabuming dalam Komunikasi Politik di Media Sosial X (Twitter) - Rizqi Nandadita Pamungkas; Permadi, Didi; Florina, Ike Desi (Universitas Indo Global Mandiri, 2024)
This research aims to analyze how the Vice President of Indonesia, Gibran Rakabuming, uses humor in political communication via the social media platform